Dupilumab in Treatment of Chronic Prurigo: A Case Series and Literature Review - Zaid Z. Almustafa; Karsten Weller; Juliane Autenrieth; Marcus Maurer; Martin Metz (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)